2019
DOI: 10.3233/ch-180467
|View full text |Cite
|
Sign up to set email alerts
|

Do two venous anastomoses decrease venous thrombosis during limb reconstruction?

Abstract: BACKGROUND:The optimal number of veins to be anastomosed in perforator flaps for limb reconstruction and its influence on the results remain controversial. Venous thrombosis of microvascular anastomoses is a commonly recorded complication in soft tissue reconstruction. OBJECTIVE: To evaluate the effect of two venous anastomoses in the incidence of venous thrombosis for limb reconstruction using anterolateral thigh (ALT) microsurgical free flaps. METHODS: This was a cross-sectional study on patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…There have been conflicting reports on whether one-or two-vein anastomoses are optimal in lower extremity flap reconstructions. Several studies showed that two-vein anastomoses reduced complication rates compared with one-vein anastomoses [3,7]. Our results indicated that the venous thrombosis rates of two-vein anastomoses were lower than those of one-vein anastomoses (8.3% versus 30%, p = 0.07), and there was little biased distribution of high-risk factors between both groups.…”
Section: Venous Outflowmentioning
confidence: 43%
See 1 more Smart Citation
“…There have been conflicting reports on whether one-or two-vein anastomoses are optimal in lower extremity flap reconstructions. Several studies showed that two-vein anastomoses reduced complication rates compared with one-vein anastomoses [3,7]. Our results indicated that the venous thrombosis rates of two-vein anastomoses were lower than those of one-vein anastomoses (8.3% versus 30%, p = 0.07), and there was little biased distribution of high-risk factors between both groups.…”
Section: Venous Outflowmentioning
confidence: 43%
“…Furthermore, end-toside (ETS) venous anastomoses have been shown to be safe with a low rate of microvascular complications in lower extremity reconstructions [5,6]. However, there is some controversy over whether one-or two-vein anastomoses offer optimal venous outflow in these reconstructions [3,4,[7][8][9]. Heterogeneity in previous studies is attributable to the inclusion of various disorders such as oncologic and traumatic defects.…”
Section: Introductionmentioning
confidence: 99%
“…Following a meticulous screening process and study exclusion, the authors identified eight studies for review (Figure 1, Table 1). Flap loss rate: Flap loss rate was reported by six studies [8,[12][13][14][15][16] in total, with comparable results between one versus two venous anastomoses in ALT flap reconstruction. No significant difference was seen with an odds ratio assessment (P > 0.5), as demonstrated in Figure 2.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…No significant difference was seen with an odds ratio assessment (P > 0.5), as demonstrated in Figure 2. Venous congestion/thrombosis: Four studies [13][14][15]17] reported venous congestion and thrombosis comparing one versus two veins, but no significant difference was seen between the two groups, as demonstrated in Figure 3 below.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation